2015
DOI: 10.1104/pp.15.00763
|View full text |Cite
|
Sign up to set email alerts
|

The Soybean-Specific Maturity Gene E1 Family of Floral Repressors Controls Night-Break Responses through Down-Regulation of FLOWERING LOCUS T Orthologs  

Abstract: Photoperiodism is a rhythmic change of sensitivity to light, which helps plants to adjust flowering time according to seasonal changes in daylength and to adapt to growing conditions at various latitudes. To reveal the molecular basis of photoperiodism in soybean (Glycine max), a facultative short-day plant, we analyzed the transcriptional profiles of the maturity gene E1 family and two FLOWERING LOCUS T (FT) orthologs (FT2a and FT5a). E1, a repressor for FT2a and FT5a, and its two homologs, E1-like-a (E1La) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
116
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(125 citation statements)
references
References 64 publications
(91 reference statements)
7
116
0
2
Order By: Relevance
“…However, genes in the FTb clade are clearly lacking in L. angustifolius , suggesting that these genes do not play an essential evolutionary role in legume photoperiod responses, and raising the question of which FT genes may mediate the photoperiod response in this species. In soybean, two genes in the FTa3 and FTc clades ( FT2a and FT5a ) (Kong et al ., ; Xu et al ., ) have prominent roles in induction of flowering by photoperiod, and our analysis of the lupin genome suggests that a minimum complement of FTa3 and FTc genes may be sufficient for both vernalization and photoperiod responsiveness. It will be interesting in future to examine which lupin FT gene(s) may be regulated by photoperiod.…”
Section: Discussionmentioning
confidence: 90%
“…However, genes in the FTb clade are clearly lacking in L. angustifolius , suggesting that these genes do not play an essential evolutionary role in legume photoperiod responses, and raising the question of which FT genes may mediate the photoperiod response in this species. In soybean, two genes in the FTa3 and FTc clades ( FT2a and FT5a ) (Kong et al ., ; Xu et al ., ) have prominent roles in induction of flowering by photoperiod, and our analysis of the lupin genome suggests that a minimum complement of FTa3 and FTc genes may be sufficient for both vernalization and photoperiod responsiveness. It will be interesting in future to examine which lupin FT gene(s) may be regulated by photoperiod.…”
Section: Discussionmentioning
confidence: 90%
“…Stable QTL for days to flowering and putative QTL for days to pod-setting were overlapped and co-localized on linkage group Pv01 (closest markers ATA3 and BMb1024), suggesting pleiotropy for genes controlling these highly correlated traits. In soybean, such a gene involved in both maturation and induction of flowering (E1 and its homologues) has been reported [54]. The overall numbers of detected QTLs for phenological traits were higher in the season of 2014, which might be associated with observed difference in timing of flowering and maturation with regard to watering conditions.…”
Section: Discussionmentioning
confidence: 97%
“…The E series of genes were shown to be important factors for plant adaptation in soybean growing regions [12], [14]. It was recently hypothesized that three of those E genes ( E1 , E3 , and E4 ) play larger roles in pre- and post-flowering photoperiod responses [11].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that E1-E4 genes are involved in regulation of both pre-flowering and post-flowering growth of plants under different photoperiod length [11]. E1 is a flowering repressor and encodes a transcription factor that contains a putative nuclear localization signal and region related to the B3 DNA-binding domain [7], [12]. E2 is an orthologue of the Arabidopsis flowering gene GIGANTEA [2], [13].…”
Section: Introductionmentioning
confidence: 99%